Biphasic epoxidation of 1-octene with H2O2 catalyzed by amphiphilic fluorinated Ti-loaded zirconia - Yun, Hau Ng; Izwan, Izan; Hadi Nur, Hadi Nur; Mohd Muhid, Mohd. Nazlan; Hamdan, Halimaton (Elsevier, 2006)
A series of amphiphilic fluorinated zirconia containing titanium was prepared by titanium impregnation followed by fluorination and alkylsilylation of zirconium oxide. Physical properties of the resulting samples were characterized by XRD analysis, UV–vis spectroscopy, BET surface area analysis and EDAX analysis. The effects of fluorine and alkylsilane groups on the samples were studied by the epoxidation of 1-octene with aqueous hydrogen peroxide. The epoxidation of alkenes is one of the most important methods of functionalizing simple hydrocarbons. The amphiphilic fluorinated catalysts were more active and more efficient than the conventional titania–silica and zirconia–silica mixed oxides in linear alkene epoxidation; enhanced by the presence of alkylsilane and fluorine groups in the catalysts. Modification with alkylsilane successfully induces the hydrophobic behavior of zirconia which is hydrophilic in nature; whereas fluorine was chosen for its electron-withdrawing effect which further activates the titanium active sites.